Sarco-endoplasmic reticulum calcium release model based on changes in the luminal calcium content - Guerrero-Hernández, Agustín; Sánchez-Vázquez, Víctor Hugo; Martínez-Martínez, Ericka; Sandoval-Vázquez, Lizeth; Perez-Rosas, Norma C.; Lopez-Farias, Rodrigo; Dagnino-Acosta, Adan (Calcium signaling, 2019)
The sarcoplasmic/endoplasmic reticulum (SR/ER) is the main intracellular calcium (Ca2+) pool in muscle and non-muscle eukaryotic cells, respectively. The reticulum accumulates Ca2+ against its electrochemical gradient by the action of sarco/endoplasmic reticulum calcium ATPases (SERCA pumps), and the capacity of this Ca2+ store is increased by the presence of Ca2+ binding proteins in the lumen of the reticulum. A diversity of physical and chemical signals, activate the main Ca2+ release channels, i.e. ryanodine receptors (RyRs) and inositol (1, 4, 5) trisphosphate receptors (IP3Rs), to produce transient elevations of the cytoplasmic calcium concentration ([Ca2+]i) while the reticulum is being depleted of Ca2+. This picture is incomplete because it implies that the elements involved in the Ca2+ release process are acting alone and independently of each other. However, it appears that the Ca2+ released by RyRs and IP3Rs is trapped in luminal Ca2+ binding proteins (Ca2+ lattice), which are associated with these release channels, and the activation of these channels appears to facilitate that the trapped Ca2+ ions become available for release. This situation makes the initial stage of the Ca2+ release process a highly efficient one; accordingly, there is a large increase in the [Ca2+]i with minimal reductions in the bulk of the free luminal SR/ER [Ca2+] ([Ca2+]SR/ER). Additionally, it has been shown that active SERCA pumps are required for attaining this highly efficient Ca2+ release process. All these data indicate that Ca2+ release by the SR/ER is a highly regulated event and not just Ca2+ coming down its electrochemical gradient via the open release channels. One obvious advantage of this sophisticated Ca2+ release process is to avoid depletion of the ER Ca2+ store and accordingly, to prevent the activation of ER stress during each Ca2+ release event.
Gesehen am 31.08.2020